Methicillin-Resistant Staphylococcus haemolyticus Displaying Reduced Susceptibility to Vancomycin and High Biofilm-Forming Ability - Dier-Pereira, Ana P.; Trevizani Thihara, Isabella Ramos; Duarte, Felipe Crepaldi; da Silva, Raquel Soares; Santos, Jussevania Pereira; Tavares, Eliandro Reis; de Oliveira, Caio Ferreira; Pinge-Filho, Phileno; Kerbauy, Gilselena; Perugini, Márcia R. E.; Yamauchi, Lucy Megumi; Yamada-Ogatta, Sueli Fumie (Infectious Disorders - Drug Targets, 2021)
Background: Staphylococcus haemolyticus is one of the most frequently coagulasenegative staphylococci isolated from healthcare-associated infections, mainly those related to implanted medical devices. Objectives: This study aimed to determine the antimicrobial susceptibility profile and biofilm forming capacity of S. haemolyticus isolated from bloodstream infections. Methods: A total of 40 S. haemolyticus isolates were characterized according to their genetic relatedness by repetitive element sequence based-PCR (REP-PCR), antimicrobial susceptibility profile, SCCmec typing, ability to form biofilm on abiotic surface and occurrence of putative genes related to biofilm formation. Results: One S. haemolyticus was susceptible to all antimicrobials. The other isolates (n=39) were resistant to cefoxitin; and among them 34 (87.2%) harbored the mecA gene into the SCCmec type I (5.9%), type III (29.4%), type IV (5.9%) and type V (20.6%); and 38.2% isolates were designated as NT. Apart from cefoxitin, 94.9% of the isolates were resistant to at least four antimicrobial classes, and 32.5% displayed minimal inhibitory concentration (MIC) values higher than 4.0 μg/mL for vancomycin. All isolates formed biofilm on polystyrene surface and were classified as strong biofilm-producers, except for one isolate. All isolates were negative for icaA gene, and the prevalence of the other genes was as follows: atl, 100%; fbp, 92.5%; aap, 90.0%; and bap, 20.0%. Conclusion: This study reports a high prevalence of methicillin-resistant S. haemolyticus displaying decreased susceptibility to vancomycin with the ability to form strong biofilms on abiotic surface. The results support the importance of controlling the adequate use of antimicrobials for the treatment of staphylococcal infections.
Keywords: coagulase-negative staphylococci